The Association of Inflammatory Markers, IL-1α and TGF-β, with Dietary Insulin Load and Dietary Insulin Index in Overweight and Obese Women with Healthy and Unhealthy Metabolic Phenotypes: A Cross-Sectional Study - Sahar Noori; Atieh Mirzababaei; Farideh Shiraseb; Reza Bagheri; Cain C. T. Clark; Alexei Wong; Katsuhiko Suzuki; Khadijeh Mirzaei (International Journal of Clinical Practice)
Context Research has shown IL-1α might play a role in the associations between the MH group and DII and DIL. Objective. We evaluated the association of inflammatory markers, IL-1α and TGF-β, with dietary insulin load and index in women with healthy and unhealthy obesity phenotypes. Materials and Methods. 228 obese/overweight women aged 18–48 years were included in this study. Biochemical factors were obtained from blood samples. Body composition, anthropometric measures, and physical activity assessments were performed. Dietary intakes, DII, and DIL were assessed. Results. Significant associations were observed between the MH group and the DII group (OR = 2.142, 95% CI = 1.421, 2.850, and p = 0.040), in which IL-1α may play a role. Discussion and Conclusion. Significant associations were observed between the MH group and DII. IL-1α might play a role in these associations.